UV Accelerates Amyloid Precursor Protein (APP) Processing and Disrupts APP Axonal Transport - Almenar Queralt, Angels (2014)
Overexpression and/or abnormal cleavage of amyloid precursor protein (APP) are linked to Alzheimer's disease (AD) development and progression. However, the molecular mechanisms regulating cellular levels of APP or its processing, and the physiological and pathological consequences of altered processing are not well understood. Here, using mouse and human cells, we found that neuronal damage induced by UV irradiation leads to specific APP, APLP1, and APLP2 decline by accelerating their secretase-dependent processing. Pharmacological inhibition of endosomal/lysosomal activity partially protects UV-induced APP processing implying contribution of the endosomal and/or lysosomal compartments in this process. We found that a biological consequence of UV-induced γ-secretase processing of APP is impairment of APP axonal transport. To probe the functional consequences of impaired APP axonal transport, we isolated and analyzed presumptive APP-containing axonal transport vesicles from mouse cortical synaptosomes using electron microscopy, biochemical, and mass spectrometry analyses. We identified a population of morphologically heterogeneous organelles that contains APP, the secretase machinery, molecular motors, and previously proposed and new residents of APP vesicles. These possible cargoes are enriched in proteins whose dysfunction could contribute to neuronal malfunction and diseases of the nervous system including AD. Together, these results suggest that damage-induced APP processing might impair APP axonal transport, which could result in failure of synaptic maintenance and neuronal dysfunction.